Pembuatan Aplikasi Lelang Berbasis Android - Lois Fernando Audi; Liliana Liliana; Agustinus Noertjahyana (Jurnal Infra, 2022)
Auction is a process of buying and selling to auction participants, where auction participants will make bids and be sold to bidders at the highest price. Today, conducting an online auction can be done through social media. Based on a survey conducted on CV Toro Developer, people still make auction transactions via Whatsapp. This auction transaction is considered inefficient, where the admin in the Whatsapp group must pay attention to the bid price entered by the auction participant. Therefore, this thesis will make an application so that auction transaction activities can be carried out without admin assistance. This thesis will focus on developing auction applications to facilitate auction transaction activities with chat features, auto bids, deposits, bid features that can be displayed in real-time, and notification features. The test results show that the application can carry out the auction process well from the beginning of creation until the transaction is complete. Also, other features can run well.